Ablation of USP21 in skeletal muscle promotes oxidative fibre phenotype, inhibiting obesity and type 2 diabetes. Issue 6 (15th September 2021) - Kim, Ayoung; Koo, Ja Hyun; Jin, Xing; Kim, Wondong; Park, Shi‐Young; Park, Sunghyouk; Rhee, Eugene P.; Choi, Cheol Soo; Kim, Sang Geon
Abstract: Background: Skeletal muscle as a metabolic consumer determines systemic energy homeostasis by regulating myofibre type conversion and muscle mass control. Perturbation of the skeletal muscle metabolism elevates the risk of a variety of diseases including metabolic disorders. However, the regulatory pathways and molecules are not completely understood. The discovery of relevant responsible molecules and the associated network could be an attractive strategy to overcome diseases associated with muscle problems. Methods: An initial screening using quantitative trait locus analysis enabled us to extract a set of genes including ubiquitin‐specific proteases21 (USP21) ( r = 0.738; P = 0.004) as potential targets associated with fasting blood glucose content. Given tight regulation of the ubiquitination status of proteins in muscle, we focused on USP21 and generated whole‐body (KO) and skeletal muscle‐specific USP21 knockout (MKO) mice. Transcriptomics, proteomics, and lipidomics assays in combination with various in vivo and in vitro experiments were performed to understand the functions of USP21 and underlying mechanisms. A high‐fat diet (60%)‐fed mouse model and diabetic patient‐derived samples were utilized to assess the effects of USP21 on energy metabolism in skeletal muscle. Results: USP21 was highly expressed in both human and mouse skeletal muscle, and controlled skeletal muscle oxidative capacity and fuel consumption. USP21‐KO or USP21‐MKO significantly promoted oxidative fibre type changes (Δ36.6% or Δ47.2%), muscle mass increase (Δ13.8% to Δ22.8%), and energy expenditure through mitochondrial biogenesis, fatty acid oxidation, and UCP2/3 induction ( P < 0.05 or P < 0.01). Consistently, cold exposure repressed USP21 expression in mouse skeletal muscle (Δ55.3%), whereas loss of USP21 increased thermogenesis (+1.37°C or +0.84°C; P < 0.01). Mechanistically, USP21 deubiquitinated DNA‐PKcs and ACLY, which led to AMPK inhibition. Consequently, USP21 ablation diminished diet‐induced obesity (WT vs. USP21‐KO, Δ8.02 g, 17.1%, P < 0.01; litter vs. USP21‐MKO, Δ3.48 g, 7.7%, P < 0.05) and insulin resistance. These findings were corroborated in a skeletal muscle‐specific gene KO mouse model. USP21 was induced in skeletal muscle of a diabetic patient (1.94‐fold), which was reciprocally changed to p‐AMPK (0.30‐fold). Conclusions: The outcomes of this research provide novel information as to how USP21 in skeletal muscle contributes to systemic energy homeostasis, demonstrating USP21 as a key molecule in the regulation of myofibre type switch, muscle mass control, mitochondrial function, and heat generation and, thus, implicating the potential of this molecule and its downstream substrates network as targets for the treatment and/or prevention of muscle dysfunction and the associated metabolic diseases.